2006
DOI: 10.1016/j.virol.2006.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated trans-acting factor of 50 kDa (Staf50) inhibits HIV-1 replication in human monocyte-derived macrophages

Abstract: In order to identify cellular genes which interfere with HIV-1 replication in monocyte-derived macrophages (MAC), cells were stimulated with interferon (IFN) or lipopolysaccharide (LPS) leading to a pronounced inhibition of HIV-1 infection in these cells, and the resulting gene expression was analyzed. Using the microarray technology we identified a gene named Stimulated Trans-Acting Factor of 50 kDa (Staf50), which is known to repress the activity of the HIV-1 LTR. Analysis of the Staf50 expression by real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
54
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 49 publications
5
54
0
3
Order By: Relevance
“…We also demonstrated that TRIM22 was a RING finger E3 ubiquitin ligase (4), and its E3 ligase activity was responsible for its antiviral activity against encephalomycocarditis virus as reported by another research group (14). Additionally, several studies indicated that TRIM22 possessed antiretroviral activity depending on certain cell types (15)(16)(17).…”
supporting
confidence: 73%
“…We also demonstrated that TRIM22 was a RING finger E3 ubiquitin ligase (4), and its E3 ligase activity was responsible for its antiviral activity against encephalomycocarditis virus as reported by another research group (14). Additionally, several studies indicated that TRIM22 possessed antiretroviral activity depending on certain cell types (15)(16)(17).…”
supporting
confidence: 73%
“…TRIM22 has been shown to interfere with HIV-1 infection by either LTR promoter repression (Tissot & Mechti, 1995), inhibition of viral replication (Bouazzaoui et al, 2006) or reduction of particle production (Barr et al, 2008). Interestingly, the C-terminal SPRY domain of TRIM proteins is proposed to be involved in protein-protein interactions and RNA binding (Hilton et al, 1998;Ponting et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…TRIM22 (also known as Staf50) was first identified to be an IFN-induced human protein that represses transcription directed by the long terminal repeat (LTR) promoter region of human immunodeficiency virus type 1 (HIV-1) (Tissot & Mechti, 1995). Recently, TRIM22 has been reported to be a natural antiviral effector of both HIV-1 replication and particle production (Barr et al, 2008;Bouazzaoui et al, 2006). The effect of TRIM22 was abolished by mutation of amino acids Cys15 and Cys18 of its RING-finger domain, suggesting that functional ubiquitin ligase activity is required for TRIM22-mediated antiviral activities.…”
mentioning
confidence: 99%
“…For example, overexpression of TRIM22 can repress the transcription initiated by the long terminal repeat (LTR) promoter of human immunodeficiency virus (HIV) type-1 and inhibit HIV-1 replication in human monocyte-derived macrophages. 15,16 Recently it was reported that TRIM22 was the key mediator for type I IFN to inhibit HIV-1 replication. 10 Additionally, TRIM22 has been implicated in normal hematopoietic differentiation and in diseases such as systemic lupus erythematosus and Wilms tumor.…”
mentioning
confidence: 99%